POTENSI PENGEMBANGAN PERHITUNGAN IKE MODEL HIBRIDA PADA BANGUNAN GEDUNG PERKANTORAN DENGAN PENDEKATAN MULTITEORI: STUDI KASUS GEDUNG MENTERI DAN GEDUNG SUMBER DAYA AIR KEMENTERIAN PEKERJAAN UMUM - Diana Kusumastuti; Erni Setyowati; Suzanna Ratih Sari; Agung Dwiyanto (Jurnal Arsitektur ARCADE, 2025)
Energy Consumption Index (IKE) is a key indicator in evaluating the energy efficiency of buildings. However, current IKE calculation methods, such as software-based simulations, are often complex, require technical expertise, and large resources, making them impractical. This study explores the potential of a hybrid model in calculating IKE by integrating six theoretical approaches to simplify the process without compromising accuracy. Case studies were conducted at the Ministry of Public Works Building and the Directorate General of Water Resources Building, focusing on benchmarking analysis of HVAC systems, lighting, and energy consumption patterns. The results show that with a multi-theoretical approach and the availability of field data, a hybrid model has the potential to be developed and applied to simplify IKE calculations, especially in the early design and energy performance evaluation stages, although there are challenges in maintaining accuracy and increasing the accessibility of the method for non-technical users. The case study shows a difference in IKE of up to 40% between the Directorate General of Water Resources Building and the Minister of Public Works Building, influenced by factors such as air conditioning systems, lighting, and elevator usage. A hybrid model based on empirical data considering the specific characteristics of each building can be an effective solution to bridge the gap between the complexity and ease of IKE calculation. Further studies are needed to integrate operational data from more buildings and optimize software-based simulations